Pengaruh Penambahan Makanan Penguat dengan Taraf Onggok dan Tepung Hijauan Ubi Kayu yang berbeda untuk Domba yang mendapat Ransum Basal Jerami Padi - L.A. Sofyan; S.I. Suwoko (Buletin Ilmu Makanan Ternak, 1987)
twenty randomly weaning lambs with average body weight 10.46 ± 1.06 kg were randomly assigned to 5 treatment (rations). The rations are differe in level of tapioca waste or onggok (0, 10, 20, 30 and 40%) and cassava-leaf (40, 30, 20, 10 and 0%) with basic composition: rice straw (37%), coconut oil meal (20%), urea (2%) and mineral mixturer (1%). The experiment was conducted with completely randomized design. Level of tapioca waste and cassava leaf were not significantly affected Dry Matter (DM) and organic matter (OM), digestibility of dry matter and organic matter daily gain, and feed efficiency. Average daily dry matter intake and organic matter intake 318.2 gram and 287.4 gram or 55.2 g/BW0.75 kg and 47 g/BW 0.75 kg respectively;average digestibility of dry matter and organic matter : 59.71 % and 58.97 %. Average daily gain: -0.48 gram and feed efficiency : -1.13%. GE and DE intake were significantly (P/_0.05) affected by level of tapioca waste and cassava leaf in the rations; GE intake were decrease with and increase of tapioca waste of decrease of cassava leaf in the ration. Minimum GE intake (1114 kkal) were obtain with 40% tapioca waste in the ration, The maximum energy digestibility were obtain with ≥20% of tapioca waste or ≥20% of cassava leaf i.e 67.82 - 68.62. The maximum digestibility energy were obtain with 20-30% tapioca waste or 20-10% cassava leaf, i,e : 1025.06 - 1084.47 kkal/head/day.